Ciało wkracza na scenę. O wypartym doświadczeniu i metaforyce cielesności - Adolphi, Rainer (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
Vindication of the body belongs to great projects of our times and the attention body receives can easily be named as one of the leitmotifs of modern age. Body has been subjected to repression, alienation and taming of its uncontrollable tendencies and wide disregard. Previous epochs left us with the dualism of mind and body, in which the spiritual element has been largely favored as the one connected to the universal truth. In recent times the situation shifted and it is the body that is seen as a source of authenticity and individuality. Attitudes towards the body have changed with the development of modern science, cultural perspective and new knowledge about body and its functions including psychosomatic and psychological. Moreover now-a-days bodies are protected like never before with new technologies. Subsequently bodies have become substituted in interaction with the outside world and estranged.